Strategies for Overcoming Emotional Challenges in the Lecture Process: Phenomenology Study of Islamic Religious Education Masters Students for the Indonesia Rise Scholarship Class (BIB) Palembang - Derri Adi Fernando; Kasinyo Harto; Ermis Suryana (UMSU, 2023)
In the transition from adolescence to adulthood, there are several life challenges for someone in the development process, especially for students who have multiple roles of responsibility. This study aims to explain what emotional challenges are most commonly experienced in the lecture process and what strategies are used to overcome emotional challenges in the lecture process by students of Islamic Religious Studies Education Masters (PAI) class of Indonesia Bangkit Scholarship (BIB) Palembang. This research method was qualitative, using a phenomenological approach to understand students' experiences and perspectives on the emotional challenges they face and the strategies they use to overcome them. The instruments used for data collection were questionnaires, interviews. The results of the study show that students of Islamic Studies Masters (PAI) class of Indonesia Bangkit Scholarship (BIB) Palembang face several emotional challenges in the lecture process, such as academic stress, insecurity, loneliness or social isolation, and personal challenges. To overcome these challenges, students use a variety of strategies, including managing their time well, developing stress management skills, seeking social support, engaging in relaxation activities such as meditation or yoga, and using campus resources such as counselling or other support services.